Survival during economic shock: the role of firm experience - Kamal, Sifat; Kamal, Shawkat (Journal of State University of Bangladesh, 2012)
Based on organizational ecology and other management theories, this paper aims at finding a relationship between organizational aging and firm survival during economic shocks. There is differing evidence on whether organizational aging has a positive or negative effect on firm survival. Thus looking at this issue, from an economic shock perspective, merits attention. After analyzing the existing literature, this study puts forward two propositions that might be used for further empirical research.